Analysis of Factors Associated with The Utilization of The Chronic Disease Program (Prolanis) in Sorong City - Nelisa Jily Pasulu; Sharon Vassilva Kapisa (CV. Publikasi Indonesia, 2026)
Chronic diseases are conditions that typically develop slowly and have a lengthy duration, as defined by the World Health Organization (WHO). Genetic, physiological, environmental, and behavioural factors are the causes of these conditions, which present concerns at the national, regional, and global levels. By 2030, an epidemiological transition from infectious diseases to non-communicable diseases is projected to occur. The purpose of this study is to determine the factors that affect the utilisation of chronic disease programs in Sorong City. This research employs a cross-sectional design and is an analytical observational study. The total sample size is 197, selected using proportional random sampling. Data analysis was conducted using SPSS version 26, encompassing chi-square tests and multiple logistic regression. The study's findings indicate that the utilisation of the chronic disease management program (Program Pengelolaan Penyakit Kronis, Prolanis) is significantly influenced by knowledge (p = 0.007), family support (p = 0.026), and support from health personnel (p = 0.014). The multivariate analysis identified knowledge (p = 0.003) and support from health personnel (p = 0.046) as the most closely associated factors, with the knowledge variable being the most significant. Community health centre staff can provide Prolanis participants with clear and accurate information about the illnesses they are managing by extending consultation time.